Three-dimensional mapping of mineral in intact shark centra with energy dispersive x-ray diffraction. (December 2022) - Park, J.S.; Chen, H.; James, K.C.; Natanson, L.J.; Stock, S.R.
Abstract: The centra of shark vertebrae consist of cartilage mineralized by a bioapatite similar to bone's carbonated hydroxyapatite, and, without a repair mechanism analogous to remodeling in bone, these structures still survive millions of cycles of high-strain loading. The main structures of the centrum are an hourglass-shaped double cone and the intermedialia which supports the cones. Little is known about the nanostructure of shark centra, specifically the relationship between bioapatite and cartilage fibers, and this study uses energy dispersive diffraction (EDD) with polychromatic synchrotron x-radiation to study the spatial organization of the mineral phase and its crystallographic texture. The unique energy-sensitive detector array at beamline 6-BM-B, the Advanced Photon Source, enables EDD to quantify the texture within each sampling volume with one exposure while constructing 3D maps via specimen translation across the sampling volume. This study maps a centrum from two shark orders, a carcharhiniform and a lamniform, with different intermedialia structures. In the blue shark ( Prionace glauca, Carcharhiniformes), the bioapatite's c -axes are oriented laterally within the centrum's cone walls but axially within the wide wedges of the intermedialia; the former is interpreted to resist lateral deformation, the latter to support axial loads. In the shortfin mako ( Isurus oxyrinchus, Lamniformes), there is some tendency for c -axis variation with position, but the situation is unclear because one dimension of the sampling volume is considerably larger than the thickness and spacing of the intermedialia's radially-oriented lamellae. Because elastic modulus in collagen plus bioapatite mineralized tissues varies significantly with both volume fraction of bioapatite and crystallographic texture, the present 3D EDD-derived maps should inform future 3D numerical models of shark centra under applied load. Graphical abstract: Image 1 Highlights: Energy dispersive diffraction mapped, in 3D, bioapatite diffracted intensity/crystallographic texture in shark vertebra. In one subvolume (cones), blue shark bioapatite c -axes were oriented laterally and elsewhere (intermedialia) axially. The blue shark crystals appear oriented to resist lateral deformation (cone) and to support axial loads (intermedialia). The shortfin mako's c -axis orientation varied with position, but a relationship with microstructure was unclear. Incorporation of EDD-derived crystallographic texture into 3D models of shark centra are discussed.